THE FOREIGN LANGUAGE E IMMERSIVE IN ENHANCING STUDENTS’ EFL SPEAKING ABILITY - Hartia Novianti; Erma Rahayu Lestari (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2019)
This study  investigates the effectiveness  of students’ EFL speaking ability, using the E Immersive  through yutube . It aims to explore whether e immersive   effective  in an English as a Foreign Language (EFL) context  is more effective  on the students’ speech development  as a teaching approach. A quasi experimental design was employed for the study. The participants  were 40 students of English department of STKIP PGRI Jombang  who were taking Speaking class in their fourth semester at STKIP PGRI Jombang.  The quantitative data were taken from students’ speaking test. The research finding revealed that the students’ achievement of experimental group in speaking ability is higher than control group and the students responses showed that they had almost positive response in taking the speaking class by employing  immersive multimedia  which reduced the use of code-switching strategies by the students and enabled them to develop oral production skills in English It implied that E immersive  learning is effective to be implemented in speaking class.